Numerical investigation of anisotropically driven developed turbulence - Hayryan, Edik; Jurcisinova, Eva; Jurcisin, Marian; Stenlik, Milan (Mathematical Modelling and Analysis, 2007)
The fully developed turbulence with axial anisotropy for dimensions d > 2 is investigated by means of renormalization group approach. The corresponding system of strongly nonlinear renormalization group equations which contain angle integrals is solved numerically. Possible utilization of the parallel programming methods is discussed. As a result, the influence of anisotropy on the stability of the Kolmogorov scaling regime is analyzed. The borderline dimension between stable scaling regime and unstable one is calculated as a function of the anisotropy parameters. Obtained results are compared with results calculated in [7].First Published Online: 14 Oct 2010